2020
DOI: 10.3389/fneur.2020.00798
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a User-Led Resource for People Transitioning to Secondary Progressive Multiple Sclerosis: Results of an International Nominal Group Study

Abstract: Background: ManTra is a mixed-methods, co-production research project for developing an intervention (resource) for people with newly diagnosed secondary progressive multiple sclerosis (pwSPMS) in Italy and Germany. In previous project actions, six resources were outlined, meeting the needs prioritized by pwSPMS. Aims: This study aims to achieve multiple-stakeholder consensus on the most suitable resource and to refine the consensus resource. Methods: Two nominal group technique (NGT) meetings were held, one i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, our study sample enabled us to gain insight into reasons for deciding against rehabilitation. However, the aspects that were discussed also cover the needs of pwMS in transition to or within a progressive phase [ 19 ]. Experiences of the six patients with SPMS did not differ qualitatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our study sample enabled us to gain insight into reasons for deciding against rehabilitation. However, the aspects that were discussed also cover the needs of pwMS in transition to or within a progressive phase [ 19 ]. Experiences of the six patients with SPMS did not differ qualitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Persons with PPMS, major cognitive deficits and/or poor German language skills were excluded from the qualitative interview study. We decided to keep patients in our study who came out as having SPMS during the interview process, since SPMS follows an initial RRMS course and the uncertain period in the transition from RRMS to SPMS can lead to difficulties in reliable distinction between RRMS and SPMS [ 19 ]. Our questions then referred to their experiences when having RRMS.…”
Section: Methodsmentioning
confidence: 99%
“…With the aim to fill the literature gap on integrated intervention for MS, the ESPRIMO project (Explore, Support, and Promote Resilience In young adults with Multiple sclerOsis) started in 2019 offering a biopsychosocial approach (i.e., ESPRIMO intervention) for young adults with MS (YawMS) aimed at improving HRQoL ( Poli et al, 2021 ; Donisi et al, 2021a , b ). The project uses a co-creation approach, thus filling a further gap considering the limited experience with participatory approaches in the MS research field ( Giovannetti et al, 2020 ). The co-creation approach aimed at adjusting and modifying ESPRIMO’s theoretical framework ( Donisi et al, 2021a ), developed based on a literature review, and to inform the content and the modalities of the intervention based on the experience, preferences and needs of the main MS stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that supporting the patient in maintaining positive hope for the future allows him to feel more “empowered,” with positive effects on quality of life and adherence (Buja et al, 2021 ). Adherence is also significantly influenced by disease-related factors such as disability, illness duration, depression, and quality of life (Giovannetti et al, 2020 ). Psychological coping has proved to be crucially important for adjusting to the adaptive demands of chronic diseases, and in the last few years, it has received growing interest in MS (Keramat Kar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%